Corruption and neo-colonialism in Latin America - Nubia Nieto (Journal of Political Science: Bulletin of Yerevan University)
Corruption is deemed one of the main drivers of development challenges in many countries, mainly in those territories that drag the shackles of colonialism. The roots of corruption in underdeveloped countries can be traced from Colonial times from South America, Asia to Africa the pattern seems to be repeated: populations subjugated to new masters, disenfranchised indigenous people, labour and sexual exploitation, brutal punishments for those who resisted colonial power were commune features for countries that experienced colonialism. Many of those power excesses have been recognised historically, however one of the most persistent element of Colonialism that survives until nowadays is corruption. The present text aims to shine a light on the relation of colonialism and corruption in Latin America. The hypothesis raised suggests that corruption was installed through colonialism in the Latin America region. The text is presented in three parts; the first one offers some historical considerations about European colonialism, the second one describes the strategies used by colonisers and the use of corruption as a tool to impose their rule and consolidate their power, and the third one exposes the new colonial form of corruption carried out by the West, led today by the United States.